STRATEGI HUMAS PEMERINTAH KABUPATEN JOMBANG DALAM MEMBANGUN KOMUNIKASI PUBLIK PADA MASA PANDEMI COVID-19 - Diana Amalia; Saifuddin Zuhri; Frida Ainun Rosyidah (Jurnal Penelitian Administrasi Publik, 2021)
Public relations is a means of information and communication for the public in every institution, both internal and external communication. Public relations has the role of providing credible information services and providing a good image for institution including government public relations. During the COVID-19 pandemic, it was a challenge for the Public Relations of Jombang District Government, because they had to implement health protocols and public services were not optimal. In addition, communication with the public must continue to be built so that people have certainty, accuracy, and adequacy of information. The formulation of the problem in scientific writing is how the Public Relations of Jombang District Government strategy in building public communication during the COVID-19 pandemic. The method used is descriptive qualitative method with data collection techniques through interviews. The results of data findings through interviews in this paper are: (a) Public Relations of Jombang District Government is refocusing program, by compiling a public communication program that aims to educate, inform the public about COVID-19 related to prevention and treatment. (b) Communicate with the public more intensely, and provides updated information through their own social media accounts, namely instagram, facebook, website and even create a instagram account for the Regent which is managed by the part of public relations. (c) To reach people who are not digitally literate, the Jombang District Government keep using radio, newspapers, magazines, and posters.